Oral treatment of human gut microbiota associated IL-10−/− mice suffering from acute campylobacteriosis with carvacrol, deferoxamine, deoxycholic acid, and 2-fucosyl-lactose - Mousavi, Soraya; Foote, Minnja S.; Du, Ke; Bandick, Rasmus; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2024)
Food-borne Campylobacter jejuni infections constitute serious threats to human health worldwide. Since antibiotic treatment is usually not indicated in infected immune-competent patients, antibioticindependent treatment approaches are needed to tackle campylobacteriosis. To address this, we orally applied carvacrol, deferoxamine, deoxycholate, and 2-fucosyl-lactose either alone or all in combination to human microbiota-associated IL-10 -/-mice from day 2 until day 6 following oral C. jejuni infection. Neither treatment regimen affected C. jejuni loads in the colon, whereas carvacrol lowered the pathogen numbers in the ileum on day 6 post-infection (p.i.). The carvacrol and combination treatment regimens resulted in alleviated diarrheal symptoms, less distinct histopathological and apoptotic epithelial cell responses in the colon, as well as diminished numbers of colonic neutrophils and T lymphocytes on day 6 p.i., whereas the latter cells were also decreased upon deferoxamine, deoxycholate, or 2-fucosyl-lactose application. Remarkably, the carvacrol, deferoxamine, and combination treatment regimens dampened ex-vivo IFN-γ secretion in the colon, the kidneys, and even in the serum to basal concentrations on day 6 p.i.. In conclusion, carvacrol alone and its combination with deferoxamine, deoxycholate, and 2-fucosyl-lactose constitute promising antibiotics-independent treatment options to fight acute campylobacteriosis.